2014
DOI: 10.1080/10548408.2014.888968
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Adoption of Travel Technology: Its Application to Unplanned Travel Behaviors

Abstract: The ultimate goal of information distribution for a destination marketer is to stimulate travelers to make a purchase decision. Today, travel information can be obtained by travel technology, which enables travelers to exploit on-the-move information. Navigation services for travel technology are being more broadly used across the globe by providing a wide range of en route information. This study evaluates the effects of travel information disseminated by navigation services on unplanned behaviors during trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Travel behavior used to be recognized as an activity involving deliberation and considerable planning, with travelers developing their plans before their trips (Hwang and Fesenmaier 2011; Kah and Lee 2014). Making travel arrangements and purchasing core tourism products and services were associated with planning (Brida and Tokarchuk 2017; Crompton 1992; Laesser and Dolnicar 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Travel behavior used to be recognized as an activity involving deliberation and considerable planning, with travelers developing their plans before their trips (Hwang and Fesenmaier 2011; Kah and Lee 2014). Making travel arrangements and purchasing core tourism products and services were associated with planning (Brida and Tokarchuk 2017; Crompton 1992; Laesser and Dolnicar 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies of the inconsistency between planned and actual behavior in tourism have been conducted since the 1980s (Chang, Stansbie, and Rood 2014; Hwang and Fesenmaier 2011; Kah and Lee 2014; March and Woodside 2005; Stewart and Vogt 1999). These studies have found that in contrast to most travel behavior models, unplanned visits are a substantial element of travel for pleasure and contribute a great deal of revenue to the local economy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…With their portability and constant connectivity, smartphones have a great influence over tourists' on-site information behavior. Mobile technologies have changed the way tourists plan their trips, highlighting the importance of research into unplanned behavior [1]. Gretzel, Zarezadeh, Li and Xiang [2] have called for theoretical advancements that can take into account new and emerging technologies.…”
Section: Introductionmentioning
confidence: 99%